Model of Caring Behavior Improvement to Achieve the Competence in Critical Care Nursing - Herdina Mariyanti; Nursalam Nursalam; Ninuk Dian Kurniawati (Jurnal Ners, 2015)
Introduction: Nursing students need to build their capacity to understand and learn the form of caring of a professional nurse from a different point of view and apply the acquired knowledge into nursing practice. The purpose of the present study was to develop a model of caring behavior improvement in students of professional nursing education program in order to achieve students’ nursing care competence.Methods: The present study used the explanatory survey and pre-experimental research design. Samples were students practicing in the ICU. Independent variables were attitude, personality, motivation and job design. Dependent variables were students’ caring behaviors and competence. Instruments used were a questionnaire for the independent variables and an observation sheet for the dependent variables. Data were analyzed using the Partial Least Square method.Results: Results showed that the loading factor of attitudes, personality, motivation, and job design against students’ caring behavior was > 1.96. The loading factor of students’ caring behaviors against the achievement of students’ competence was > 1.96. There were effects of attitude, personality, motivation and job design on students’ caring behaviors. Additionally, there was a signifi cant effect of caring behaviors on the achievement of student competence.Conclusion: students’ attitudes, personality, motivation and job design would affect the shaping of students’ caring behaviors. Students’ caring behaviors would affect the achievement of student competence.